2016
DOI: 10.1016/j.neulet.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Religious and spiritual importance moderate relation between default mode network connectivity and familial risk for depression

Abstract: Individuals at high risk for depression have increased default mode network (DMN) connectivity, as well as reduced inverse connectivity between the DMN and the central executive network (CEN) (Posner et al., 2015). Other studies have indicated that the belief in the importance of religion/spirituality (R/S) is protective against depression in high risk individuals (Miller et al., 2012). Given these findings, we hypothesized that R/S importance would moderate DMN connectivity, potentially reducing DMN connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 29 publications
3
36
0
Order By: Relevance
“…Miller et al, 1997, 2012). It has also proven to be able to distinguish groups that differ in brain structure (Miller et al, 2013), function (Peterson et al 2014; Svob et al, 2016), and EEG (Tenke et al, 2013). The present report affirms the original EEG findings using stronger measures, and unambiguously characterizes posterior EEG alpha as the biomarker identified by R/S importance.…”
Section: Discussionmentioning
confidence: 99%
“…Miller et al, 1997, 2012). It has also proven to be able to distinguish groups that differ in brain structure (Miller et al, 2013), function (Peterson et al 2014; Svob et al, 2016), and EEG (Tenke et al, 2013). The present report affirms the original EEG findings using stronger measures, and unambiguously characterizes posterior EEG alpha as the biomarker identified by R/S importance.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent studies on the same participants, we found increased default mode network (DMN) connectivity (Posner et al, ), and greater EEG alpha among individuals at high (compared to low) familial risk for depression (Tenke et al, ). However, within the subgroup of individuals at high risk for depression, those reporting that R/S was highly important to them had reduced DMN connectivity (Svob, Wang, Weissman, Wickramaratne, & Posner, ) and greater EEG alpha (Tenke et al, ). In other words, brain differences associated with importance of R/S beliefs were the opposite of those associated with disease risk, suggesting that R/S may provide a compensatory mechanism or buffering effect.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies documented that women and divorced individuals were much more likely to have depressive symptoms (Akhtar-Danesh & Landeen, 2007). In addition, education and religious belief were regarded as a protective effect against anxiety and depression (Bjelland et al, 2008;Svob, Wang, Weissman, Wickramaratne, & Posner, 2016).…”
mentioning
confidence: 99%